PENGARUH KONSENTRASI ABSORBEN (Fe-EDTA) TERHADAP PENURUNAN KANDUNGAN H2S DALAM BIOGAS PADA LAJU ALIR UDARA REGENERASI YANG BERBEDA - Endang Kwartiningsih; Arif Jumari; Adrian Nur; Danu Nugroho; Umi Sarwanti; Slamet Sapto; Endah Ari (Eksergi, 2008)
Bíogas is very potential to be used as fuel because of its high content of methane. Biogas had also been developed and used by several industries as alternative fuels to substitute mineral oil, The disadvantage of biogas as fuel was its high content of hydrogen sulfide which is potentíal to pollute the ervironment. Because of this, biogas should be purified first before being used as fuel. Generally, the content of H2S can bereduced physically, chemically or biologically methods, but these methods have many disadvantages. Biogas purílìcation(also other gases) from the content of H2S using Fe-EDTA(Iron Chelated Solution) gave several advantages. The advantages were the absorbent solution can be regenerated that means a cheap operation cost, the separated sulfur was asolid (that is an economic commodity) or resídue that is easy to handle and is save to be disposal to environment. Iron Chelated Solutionwas made by solving the substance of salted iron to EDTA solution. The salt of FeCl2, was made by solving iron waste obtained from lathe machine to hydrochloric acid solution. The research of reduction of the content of H2S in biogas was conducted by contacting Fe-EDTA solution with biogas in an absorber column of 1 m height and 0. I m diameter The rich H2S solution from absorber was then flowed to the separator column to separate the solid of sulfur and its solution. The solution from separator column was then regenerated by oxidation in regenerator column. In regenerator column solution which is rich of iron reacted with oxygen from air to be Fe3. . The solution which is rich of Fe was then used again to absorb H2S in biogas. Biogas used during experiment was obtained from PT Indo Acidatama Tbk. The content of H2S in raw biogas was 2.8235 %. The result of the research showed that the concentration of absorbent influenced the reduction of the content of H2S. Absorbent solution with concentration of 0.2 M of Fe-EDTA was able to absorb 99 % of all H2S from 2.8235 % to 0.02 % in a column of I m height and 0.1 m diameter Absorbent solution with concentratíon of 0.1 M of Fe-EDTA was only able to absorb 59% of all H2S from 2.8235% to 1.2 %. The regeneration air flow rate also influence the reduction of the content of H2S in biogas. The higher the regeneration airflow rate the higher the reduction of the content of H2S.